Harta Benda dalam Perkawinan - Ulya Shafa Firdausi; Dian Rosita; Arina Novitasari; Maslikan, Maslikan (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Marriage is a physical and spiritual bond between a man and a woman, aimed at forming a happy and lasting family. In marriage, property plays a crucial role and is legally classified as either joint property or personal property, as regulated in Law No. 1 of 1974 and the Compilation of Islamic Law (KHI). However, property ownership often becomes a source of conflict, sometimes leading to divorce.The legal status of property after divorce depends on the applicable legal framework, whether Islamic law, customary law, or the Civil Code (KUHPerdata). To prevent disputes, couples may establish a prenuptial agreement to regulate property ownership and division. This study employs a normative juridical method by analyzing primary, secondary, and tertiary legal materials. The research aims to provide an understanding of the legal status of property in marriage and the importance of prenuptial agreements in avoiding conflicts and ensuring a harmonious household.